Transparent Graphene-Based RIS for 6G Communications in the THz Spectrum - I. Marasco; C. Cantore; G. V. Bianco; G. Bruno; A. D'Orazio; G. Magno (IEEE Open Journal of Antennas and Propagation)
In the quest for sixth-generation wireless communication technology (6G), Terahertz waves represent a key technology due to their distinct advantages over microwaves and infrared radiation. Reconfigurable intelligent surfaces (RIS) emerge as a critical technology within this context. This paper presents a numerical investigation and the optimized design of a transparent graphene-based RIS operating in the THz spectrum. The aim of the paper is twofold: the former is to demonstrate the reconfigurability of the proposed RIS by exploiting two methods, referred to as “digital” and “analogical”. The latter is to demonstrate the effects of the losses and of the mutual coupling among unit cells on the power flow pattern. This aspect is crucial in the design of the RIS and cannot be overlooked, differently from other papers reported in the literature which analyze the RIS as an “ideal” structure evaluating only an analytical estimation of the array factor and neglecting the interaction among the unit cells. Our results hold significant promise for improving the development of a new class of smart devices crucial for 6G wireless communication systems.